THE GEOLOGICAL FACULTY OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV: THE DEANS - Gryshchuk, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article is a tribute to the deans’ contribution to increasing the profile of the Geological Faculty, as well as their academic and scientific achievement. Personnel records were used as the main source of information about the deanship to compile data on the personalities and their administrative, academic and scientific work. The result is a chronological account of the faculty leaders’ activities tracing the evolution of the geological department at Kyiv University: Geology and Geography (1933-1944), Geology and Edaphology (1944-1949) and, finally, Geology (1949). The article outlines the most important stages in the development of the geological department of Kyiv University since it was founded in 1933 to May 2014. Reference material about the deans of the faculty includes details of their qualifications, managerial, scientific and social activities, improving the strategy and schemes of geological training, major works and awards.